1)I thought you bring everything to one side: -4x^3+7x^2-10x-9=0
2) then you factor: x^2(-4x+7)-10x+9=0
3) then set everything to zero: (-4x+7)=0 x^2-10x+9=0
4) then solve: X=7/4. X=9 x=1
Is that not right? What did I do wrong? >_<
1)I thought you bring everything to one side: -4x^3+7x^2-10x-9=0
2) then you factor: x^2(-4x+7)-10x+9=0
3) then set everything to zero: (-4x+7)=0 x^2-10x+9=0
4) then solve: X=7/4. X=9 x=1
Is that not right? What did I do wrong? >_<
1)I thought you bring everything to one side: -4x^3+7x^2-10x-9=0
2) then you factor: x^2(-4x+7)-10x+9=0
3) then set everything to zero: (-4x+7)=0 x^2-10x+9=0 this step is incorrect ... one sets factors equal to zero, not terms.
4) then solve: X=7/4. X=9 x=1 Is that not right? What did I do wrong? >_<